Turning into the wind: COVID-19 as a catalyst for creativity in higher education (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
In this short essay, the author addresses challenges facing higher education in the COVID-19 era and how they may precipitate positive change and much-needed creativity.